Pengaruh Aksesibilitas, Amenitas Dan Ansilari Terhadap Kepuasan Pengunjung Pada Destinasi Wisata Bukit Cendana (Studi Pada Pengunjung Destinasi Bukit Cendana Pesawaran) - Novita, Nanda Ayu; Rosilawati, Weny; Nurhayati, Nurhayati (Universitas Mitra Indonesia, 2024)
This research aims to find out how much influence accessibility, amenities and ancillary have on tourist satisfaction at the Cendana Hill Tourist Destination. The background to this research is that there is still a lack of tourist satisfaction with the services provided by destination managers, apart from that, road access to the destination still has shortcomings.This research uses quantitative research methods. The data used are primary and secondary data. Data was collected using questionnaires distributed to tourist to the destination as many as 96 respondents. The collected data was analyzed using the SPSS 25 analysis method.The research results show that there is a positive and significant influence on accessibility on tourist satisfaction. The research results show a positive and significant influence on amenities on tourist satisfaction. And finally, the results of this research show that there is a positive and significant influence on tourist satisfaction at the Bukit Cendana tourist destination. Accessibility, amenities and amenities show a significant influence on tourist satisfaction. Keywords : Accessibility, Amenities, Ancillary, Tourist Satisfaction